2017
DOI: 10.1111/josi.12208
|View full text |Cite
|
Sign up to set email alerts
|

Poor but Warm, Rich but Cold (and Competent): Social Classes in the Stereotype Content Model

Abstract: Social class divides worsened during and after the Great

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
170
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 189 publications
(203 citation statements)
references
References 35 publications
(44 reference statements)
17
170
1
5
Order By: Relevance
“…It has been suggested that these exaggerated stereotypes found in more unequal countries further legitimize negative treatment of the poor [19] and we predict that it will be associated with so-called "classism" (i.e., enhanced stereotyping of different wealth groups [20]). Further work is needed to complement the anecdotal and qualitative research that has provided initial support for this prediction [21].…”
Section: Why Income Inequality Is Harmful For Intergroup Relations Inmentioning
confidence: 79%
See 1 more Smart Citation
“…It has been suggested that these exaggerated stereotypes found in more unequal countries further legitimize negative treatment of the poor [19] and we predict that it will be associated with so-called "classism" (i.e., enhanced stereotyping of different wealth groups [20]). Further work is needed to complement the anecdotal and qualitative research that has provided initial support for this prediction [21].…”
Section: Why Income Inequality Is Harmful For Intergroup Relations Inmentioning
confidence: 79%
“…Durante et al [18,19] provides some initial evidence for this hypothesis. In a study including 37 samples from 27 nations, it was found that higher inequality lowered warmth perceptions of those higher in socio-economic status and led to increased incompetence perceptions of people lower in SES [19].…”
Section: Why Income Inequality Is Harmful For Intergroup Relations Inmentioning
confidence: 97%
“…For example, the stereotype content model (Fiske, Cuddy, Glick, & Xu, 2002) has examined stereotypes of high-and low-income individuals (Durante, Tablante, & Fiske, 2017) and can account for the way people rationalize social relations between groups. Such rationalizations are strongest in nations experiencing high levels of inequality (Durante et al, 2012).…”
Section: Factors Related To Perceptions Of Inequalitymentioning
confidence: 99%
“…Rich people, as a salient societal group, are cross-nationally (37 samples in 27 nations) stereotyped as more competent (but colder) than poor people, especially under conditions of greater income inequality [5]. In contrast, poor people are stereotyped as lazy and substance abusers in the US [6] as well as in the egalitarian Sweden [7].…”
Section: Social-class Stereotype Contentmentioning
confidence: 99%